Jesus and the Gospel in Africa: History and Experience - Bediako, Kwame (Orbis Books, 2004)
"Jesus and the Gospel in Africa collects writings by Kwame Bediako and is the best source for his insights into the Christ of present-day African history and the Jesus of African faith. Bediako shows how intimately bound together are such elements as the message of Jesus and the struggle to give birth to African democracy." –Book Jacket.
Keywords: History / Africa / General; Religion / Christianity / History